Critical heat flux at flow boiling of refrigerants in minichannels at high reduced pressure. (July 2018) - Belyaev, A.V.; Varava, A.N.; Dedov, A.V.; Komov, A.T.
Highlights: The CHF at high reduced pressure in a minichannel are obtained. Qualitative differences were not observed between the CHF data in a minichannel and the results obtained in conventional tubes. Abstract: This paper presents an experimental setup along with experimental data for critical heat flux. The hydraulic loop of the experimental setup allows it to maintain stable flow parameters at the inlet of the test section at pressures up to 2.7 MPa and temperatures up to 200 °C. Experiments on hydrodynamics and heat transfer were performed for R113 and RC318 in two vertical channels with diameters of 1.36 and 0.95 mm and lengths of 200 and 100 mm, respectively. The inlet pressure-to-critical pressure ratio (reduced pressure) was pr  =  p/pcr  = 0.15–0.9, the mass flux was between 700 and 4800 kg/(m 2  s), and the inlet temperature varied from 30 to 180 °C. The primary regimes were obtained for conditions ranging from highly subcooled flows to saturated flows. For each regime with fixed parameters, the maximum possible heating power value was applied, with the maximum value limited by the maximum output of the power supply, the onset of dryout, or wall temperatures exceeding 350 °C. The influences of flow conditions (i.e., mass flow rate, pressure, inlet temperature, and channel diameter) on the critical heat flux and a comparative analysis of different methods of data generalization are presented.